THE INFLUENCE OF SERVICE QUALITY, BRAND IMAGE AND ACCESSIBILITY ON HOTEL CUSTOMER SATISFACTION IN INDONESIA - Wahyu Agus Triono; Jamaludin Khalid (Strategic Management Business Journal, 2023)
This study was conducted to determine the influence of service quality, brand image, accessibility on customer satisfaction at Amaris hotel Panglima Polim 2. This study used the multiple linear regression method. The population data used in this study were customers of Amaris Hotel Panglima Polim 2 which amounted to 100 respondents using quantitative. The data used in this study used primary data collected directly from respondents. The collected data is processed using the SPSS version 25 application, including validity tests, reliability tests, data normality tests, heterochedasisity tests, multi-collinearity tests, linearity tests, multiple linear regression tests, t tests and f tests. From this research, it proves that the quality of service affects customer satisfaction, brand image and accessibility do not affect customer satisfaction. Then the quality of service, brand image, and accessibility simultaneously affect customer satisfaction at Amaris Hotel Panglima Polim 2. JEL Classification: M21, M31